Drinking behavior among older adults in a planned retirement community: results from The Villages survey. (5th October 2015) - Fishleder, Sarah; Schonfeld, Lawrence; Corvin, Jaime; Tyler, Susan; VandeWeerd, Carla
Abstract : Objectives: Research indicates increasing trends among older adults toward heavy and abusive drinking, often associated with depressive symptoms. Possible exceptions are residents of planned retirement communities, whose drinking may be associated with social activities. To better understand these relationships, this study examined the relationship of depressive symptoms and drinking in a large retirement community. Methods: The Villages, a retirement community in central Florida with a focus on healthy, active living, has almost 90 000 residents. In 2012, a population‐based needs assessment was conducted in partnership with University of South Florida Health. In the present study, 11 102 surveys were completed and returned. A structural equation model was utilized to analyze the relationship between depressive symptoms and alcohol use as measured by the three‐item Alcohol Use Disorders Identification Test (AUDIT‐C). Results: Hazardous drinking was reported in 15.4% of respondents, somewhat higher than the general population of older adults (around 10%). Variables of depressive symptoms, physical activity, total health problems, and poor general health loaded significantly into the factor of depression indicators, which was shown to have a significant, negative correlation with risk of hazardous drinking ( λ = 0.16, p < 0.000, R 2 = 0.02). Conclusions: Results suggest at‐risk drinking among respondents was not associated with depression, in contrast to studies of older adults living alone where alcohol abuse was often associated with depression. Implications for successful aging are discussed. Copyright © 2015 John Wiley & Sons, Ltd.